Nogo presence is inversely associated with shifts in cortical microglial morphology following experimental diffuse brain injury. (17th September 2017) - Ziebell, Jenna M.; Ray-Jones, Helen; Lifshitz, Jonathan
Highlights: Diffuse traumatic brain injury is associated with inflammation and reduced myelin antigenicity. Diffuse brain injury shifts the distribution of microglia morphologies. NEP(1–40) treatment shifted microglia proportions away from ramified to fully activated/macrophage. Myelin by-products resulting from brain injury impact microglia distributions. Abstract: Diffuse traumatic brain injury (TBI) initiates secondary pathology, including inflammation and reduced myelination. Considering these injury-related pathologies, the many states of activated microglia as demonstrated by differing morphologies would form, migrate, and function in and through fields of growth-inhibitory myelin byproduct, specifically Nogo. Here we evaluate the relationship between inflammation and reduced myelin antigenicity in the wake of diffuse TBI and present the hypothesis that the Nogo-66 receptor antagonist peptide NEP(1–40) would reverse the injury-induced shift in distribution of microglia morphologies by limiting myelin-based inhibition. Adult male rats were subjected to midline fluid percussion sham or brain injury. At 2 h, 6 h, 1 d, 2 d, 7 d, and 21 d post-injury, immunohistochemical staining was analyzed in sensory cortex (S1BF) for myelin antigens (myelin basic protein; MBP and CNPase), microglia morphology (ionized calcium-binding adapter protein; Iba1), Nogo receptor and Nogo. Pronounced reduction in myelin antigenicity was evident transiently at 1 d post-injury, as evidenced by decreased MBP and CNPase staining, as well as loss of white matter organization, compared to sham and later injury time points. Concomitant with reduced myelin antigenicity, injury shifted microglia morphology from the predominantly ramified morphology observed in sham-injured cortex to hyper-ramified, activated, fully activated, or rod. Changes in microglial morphology were evident as early as 2 h post-injury, and remained at least until day 21. Additional cohorts of uninjured and brain-injured animals received vehicle or drug (NEP(1–40), i.p., 15 min and 19 h post-injury) and brains were collected at 2 h, 6 h, 1 d, 2 d, or 7 d post-injury. NEP(1–40) administration further shifted distributions of microglia away from an injury-induced activated morphology toward greater proportions of rod and macrophage-like morphologies compared to vehicle-treated. By 7 d post-injury, no differences in the distributions of microglia were noted between vehicle and NEP(1–40). This study begins to link secondary pathologies of white matter damage and inflammation after diffuse TBI. In the injured brain, secondary pathologies co-occur and likely interact, with consequences for neuronal circuit disruption leading to neurological symptoms.